The Vintage Teacup Club - Greene, Vanessa (London Sphere, 2012)
"Three women's lives are about to change because of a few delicate pieces of china... Jenny Davis comes across a beautiful vintage tea set at an outdoor market in the English countryside, she's convinced it's fate. A young bride on a budget, she has her heart set on a vintage tea-party theme for her wedding-and the gorgeous gold-rimmed china before her is perfect. There's only one problem. Two other women have fallen in love with it, too. So they come up with a solution: They'll share it. They establish a sisterhood, sharing the ups and downs of their lives-from broken hearts and weddings, to family drama and career dreams. When a figure from Jenny's past threatens to ruin her big day, Alison's teenage daughter pushes her to the limit, and Maggie's romantic life is thrown into turmoil, the members of the Vintage Teacup Club band together-proving their newfound friendship will last a lifetime. "-- Provided by publisher.
Previously published as "Sphere trade paperback edition / October 2012" -- Title page verso.
UCWS-3381g donated by Adrienne Maguddayao - February 2018
Keywords: Female friendship -- Fiction; Sharing -- Fiction; Life change events -- Fiction; FICTION / Contemporary Women; Domestic fiction